Peran mediasi kapabilitas ambidextrous pada hubungan learning agility dan kinerja bisnis UMK di Indonesia - Petiana Indriati (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the relationship between learning agility and business performance in 221 MSMEs in Jakarta, considering the mediating role of ambidextrous capability. Using covariance-based structural equation modeling (CB-SEM) through JAMOVI, the results indicate that learning agility significantly influences the development of ambidextrous capability, which in turn positively impacts business performance. The findings reveal that most of the influence of learning agility on business performance occurs indirectly through ambidextrous capability, emphasizing the importance of a balance between exploration and exploitation activities. Practically, this study recommends the development of an organizational learning system that fosters adaptability, the establishment of a structure that balances innovation and efficiency, and the creation of a conducive organizational culture. The study's findings provide practical contributions to MSMEs, enhancing their competitiveness in a dynamic business environment.